SAYYID OTALIQ MADRASA (World Bulletin of Social Sciences, 2026)
This article examines the history, construction period, architectural structure, and historical significance of the Sayyid Otaliq Madrasa located in the city of Denov in the Surkhandarya region. During the research process, historical sources, scientific literature, and local materials were analyzed to reveal the circumstances of the madrasa’s construction and its role in the spiritual and educational life of Denov. The study also provides information about the architectural features of the madrasa complex, its place within the system of twin architectural structures, the damage it suffered during the Soviet period, and the restoration work carried out during the years of independence. The research results demonstrate that the Sayyid Otaliq Madrasa is one of the important historical and architectural monuments of the Surkhan oasis.